Role of Sonographic Imaging in Occupational Therapy Practice - Roll, Shawn C. (Am J Occup Ther, 2015)
Occupational therapy practice is grounded in the delivery of occupation-centered, patient-driven treatments that engage clients in the process of doing to improve health. As emerging technologies, such as medical imaging, find their way into rehabilitation practice, it is imperative that occupational therapy practitioners assess whether and how these tools can be incorporated into treatment regimens that are dually responsive to the medical model of health care and to the profession’s foundation in occupation. Most medical imaging modalities have a discrete place in occupation-based intervention as outcome measures or for patient education; however, sonographic imaging has the potential to blend multiple occupational therapy practice forms to document treatment outcomes, inform clinical reasoning, and facilitate improved functional performance when used as an accessory tool in direct intervention. Use of medical imaging is discussed as it relates to occupational foundations and the professional role within the context of providing efficient, effective patient-centered rehabilitative care.